2017
DOI: 10.3389/fcimb.2017.00340
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin and Toltrazuril Are Able to Reduce Toxoplasma gondii Growth in Human BeWo Trophoblastic Cells and Villous Explants from Human Third Trimester Pregnancy

Abstract: Classical treatment for congenital toxoplasmosis is based on combination of sulfadiazine and pyrimethamine plus folinic acid. Due to teratogenic effects and bone marrow suppression caused by pyrimethamine, the establishment of new therapeutic strategies is indispensable to minimize the side effects and improve the control of infection. Previous studies demonstrated that enrofloxacin and toltrazuril reduced the incidence of Neospora caninum and Toxoplasma gondii infection. The aim of the present study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 72 publications
3
52
0
5
Order By: Relevance
“…Moreover, we showed that oleoresins (C. duckei and C. pubiflora) increase the MIF levels by uninfected cells. In agreement with the literature, T. gondii infection increased MIF production 33 . However, the treatment with oleoresins from C. duckei (32 µg/mL), C. paupera (64 and 32 µg/mL), and C. pubiflora (32 µg/mL) reduced MIF production by parasite-infected BeWo cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, we showed that oleoresins (C. duckei and C. pubiflora) increase the MIF levels by uninfected cells. In agreement with the literature, T. gondii infection increased MIF production 33 . However, the treatment with oleoresins from C. duckei (32 µg/mL), C. paupera (64 and 32 µg/mL), and C. pubiflora (32 µg/mL) reduced MIF production by parasite-infected BeWo cells.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, C. pubiflora oleoresin appeared to be more efficient in the inhibition of parasite growth than classical drugs (SDZ + PYR). As expected, SDZ + PYR treatment did not show cytotoxicity in villous explants and inhibited the intracellular proliferation of the parasites 33 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations